Phasenfeldmodellierung von Bruchbildungs-, Kristallisations- und Auflösungsvorgängen in hydrothermalen Umgebungen - Späth, Michael (Schriftenreihe des Instituts für Angewandte Materialien, Karlsruher Institut für Technologie, 2022)
This work focuses on the numerical investigation of fracture formation, crystallization, and crystal dissolution processes in subsurface hydrothermal environments on microscale. Phase-field models are presented and applied to these processes. The formation of mineral veins in limestones and in quartz-rich microstructures are modeled to investigate different factors which influence the evolving crystal structure. Moreover, crystal dissolution processes of different minerals are modeled.